The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1136/vr.124.15.395
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pregnancy and prediction of fetal age in red deer by real-time ultrasonic scanning

Abstract: Sixteen pregnant red deer hinds were scanned using real-time ultra sound at regular intervals during the first 150 days of pregnancy. In the early stages of pregnancy, an intra-rectal linear array transducer was used but later in pregnancy the hinds were scanned externally with a sector scanner. Pregnancy was determined from 30 days of gestation by intra-rectal scanning, and from 50 days by external scanning. With advancing age the size of the fetus increased, and linear regressions of size on age gave residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The head width, or biparietal diameter (BPD), was widely measured in the human and was mainly measured in the animal. In small ruminants during pregnancy, ultrasoundderived BPD data have been reported for various breeds of goats [8][9][10]17], sheep [1,5,10] and red deer [2,23]. Haibel [8] reported that BPD was significantly increased with gestational age in dairy goats (r 2 =0.9811).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The head width, or biparietal diameter (BPD), was widely measured in the human and was mainly measured in the animal. In small ruminants during pregnancy, ultrasoundderived BPD data have been reported for various breeds of goats [8][9][10]17], sheep [1,5,10] and red deer [2,23]. Haibel [8] reported that BPD was significantly increased with gestational age in dairy goats (r 2 =0.9811).…”
Section: Discussionmentioning
confidence: 93%
“…Measurement of fetal trunk diameter by ultrasonography was used generally for assessment of gestational ages in human and animals. However, in small ruminants, it was reported only in ewe [1] and red deer [2,23]. Aiumlamai et al [1] reported that coefficient value of fetal trunk diameter against gestational age in ewes was significant (r=0.80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, on August 27 th 2009, hinds were divided in three groups for breeding so that each group was assigned to five stags which were maintained during a month and removed from the herds on September 29 th . Two months after the males were removed from the groups of hinds, these were examined by rectal ultrasonography using a ultrasonic equipment Aloca 500 SSD with a 7.5 MHz probe Since positive diagnosis was made by direct observation and measurement of foetal structures (crownrump length, head length, head diameter, nose length, chest depth, chest width) then we considered that sensitivity was 100% like those data reported by other authors (White et al, 1989;Bingham et al, 1990). Anyway, the degree of specificity and accuracy of our results can be considered high and this indicates that from two to three months gestation onwards the transrectal technique can be used very reliably.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography has been used for pregnancy diagnosis and fetal measurement in a number of cervid species, such as red deer, fallow deer and reindeer (Rangifer tarandus) [22][23][24][25][26][27][28][29]. In red deer, regression lines are available for fetal age estimation that were obtained by measuring various dimensions of fetuses of known age using ultrasonography as early as day 24 of pregnancy [24,27].…”
mentioning
confidence: 99%